Population Dynamics of Brinjal Whitefly (Bemisia tabaci Gennadius) and Jassid (Amrasca biguttula biguttula Ishida) and Their Correlation with Abiotic Factors - Kheev Raj,; Lekhu Gehlot, (The Bioscan, 2025)
An investigation was carried out to study the population dynamics of brinjal whitefly (Bemisia tabaci Gennadius) and jassid (Amrasca biguttula biguttula Ishida) and their relation to abiotic parameter in simple plots with at a local farm in the Jodhpur region in Rajasthan, which is situated at an altitude of 26°13 N and a longitude of 73°04 E. The brinjal variety MEBH -10 was cultivated in simple plot during the summer season 2023. During the crop season the jassid and whitefly population was recorded first on fourth week of April and reached to its peak (15.50 jassids/6leaf and 15.50 whiteflies/6leaf) during the third & first week of June, when the mean temperature and relative humidity ranged from 19 °C to 46 °C and 18 to 98 per cent, respectively. The jassids shows positive correlation with maximum temperature, relative humidity, minimum temperature and rainfall. The whiteflies showed positive correlation with maximum and minimum temperature, relative humidity and rainfall.